1994
DOI: 10.1161/01.hyp.23.6.976
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of porcine coronary artery to bradykinin. Role of arachidonic acid.

Abstract: Bradykinin-induced relaxation of precontracted, porcine coronary artery (PCA) rings is mediated by distinctly different endothelium-derived relaxing factors depending on the contractile agent used. Thus when contracted with KC1, bradykinin-induced relaxation of PCA rings is mediated solely by nitric oxide (NO), whereas when contracted with the thromboxane mimetic U46619, a small component of the relaxation is attributable to NO and a large component is attributable to a non-NO mechanism that is independent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…Furthermore, in some vascular beds, cytochrome P450 inhibitors inhibit endothelium-dependent vasorelaxation resistant to cyclo-oxygenase and nitric oxide synthase blockade, although in these studies, the membrane potential was not measured Bauersachs et al, 1994;Fulton et al, 1995). In the present study, different cytochrome P450 inhibitors (SKF525a, metyrapone, clotrimazole, 17-ODYA and methoxsalen) did not inhibit the hyperpolarization produced by acetylcholine, although the concentrations studied were equivalent to or even higher than that used by other authors to block endothelium-dependent relaxations Bauersachs et al, 1994;Oyakan et al, 1994;Weintraub et al, 1994;Fulton et al, 1995). These results were confirmed by the absence of inhibitory effect of ETYA, a non specific inhibitor of lipoxygenases/cyclo-oxygenases/cytochrome P450 monooxygenases and quinacrine and an inhibitor of phospholipase A2.…”
Section: Statisticscontrasting
confidence: 46%
“…Furthermore, in some vascular beds, cytochrome P450 inhibitors inhibit endothelium-dependent vasorelaxation resistant to cyclo-oxygenase and nitric oxide synthase blockade, although in these studies, the membrane potential was not measured Bauersachs et al, 1994;Fulton et al, 1995). In the present study, different cytochrome P450 inhibitors (SKF525a, metyrapone, clotrimazole, 17-ODYA and methoxsalen) did not inhibit the hyperpolarization produced by acetylcholine, although the concentrations studied were equivalent to or even higher than that used by other authors to block endothelium-dependent relaxations Bauersachs et al, 1994;Oyakan et al, 1994;Weintraub et al, 1994;Fulton et al, 1995). These results were confirmed by the absence of inhibitory effect of ETYA, a non specific inhibitor of lipoxygenases/cyclo-oxygenases/cytochrome P450 monooxygenases and quinacrine and an inhibitor of phospholipase A2.…”
Section: Statisticscontrasting
confidence: 46%
“…However, it should be noted that these experiments were done in bovine arteries. Weintraub et al reported that the nature of acetylcholine-induced EDHF in porcine coronary arteries may not be a metabolite of cyclooxygenase or cytochrome P450 monooxygenase (27). Corriu et al reached the same conclusion with the guinea pig carotid artery (28).…”
Section: Discussionmentioning
confidence: 83%
“…3,4,[15][16][17][18][19] Optical techniques, such as fluorescence 16,20,21 or luminescence, 18,22,23 take advantage of the native optical properties of the therapeutic or conjugation of tracer molecules. Electrophysiological approaches, such as voltage-clamp techniques, 19,24,25 directly assess the changes in membrane potential provoked during UMDD, but often require isolated cells cultured in vitro, where cellular processes can vary from in vivo conditions.…”
Section: Drug Delivery Quantificationmentioning
confidence: 99%
“…Isolated tissue bath perfusion systems have been used extensively to characterize contractility changes induced by a therapeutic 20,[29][30][31][32][33] in a variety of muscular tissue beds, including gastric, 1,2,12-14 peripheral vascular, 3,4,[15][16][17][18][19] and cardiovascular 16,20,21 beds. In these systems, dosedependent changes in active muscular tension can be characterized in response to vasorelaxing agents such as bradykinin, 18,22,23 sodium nitroprusside, 19,24,25 nitroglycerin, [26][27][28] and NO.…”
Section: Drug Delivery Quantificationmentioning
confidence: 99%
See 1 more Smart Citation